Influence of activated carbon for adsorption and removal of impurities in fuel ethanol stored in stationary A36 carbon steel tanks (Research, Society and Development, 2025)
The storage of sugar-energy production is an important factor in the logistics of biofuel distribution, from the storage of products in the agroindustry to sale to the final consumer, where possible environmental impacts must be observed, as well as the quality of the product to be made available by gas stations. Waste from these processes can be the result of corrosive processes that end up accumulating over time inside these fuel tanks, altering the quality of the biofuel. Another factor considered is the economic value, that is, the financial impact due to biofuel contamination and the reduction in the effective mass of the tanks. In view of this, the evaluation of impurity removal processes, which contribute to the oxidation of fuel hydrated ethyl alcohol storage tanks, and the separation of accumulated waste not only contribute to the detection and control of changes caused in the physical-chemical specifications of the fuel, but are also of great importance in terms of environmental and economic impacts. The present research aims to verify the deviations from the standardized conformity experienced by hydrated ethanol while stored and in order to reduce the amount of material to be discarded, after separating the contaminants that promote changes in the quality of the product, deviating from legal specifications and applications. Using materials such as activated carbon, which are low cost and easy to use, it is expected to reduce the volume of product to be discarded and guarantee the quality of the recovered ethyl alcohol, adjusting it so that it meets the specifications of current legislation and is ready to be sold.